KARISMA DAN TANGGUNG JAWAB KEPALA SEKOLAH DI ERA DISRUPSI PENDIDIKAN SEKOLAH KATOLIK - Eko Susanto, Andrias; Oktarina, Nina; Rokhman, Fathur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The current digital millennial era is an era where the world is facing the phenomenon of large and rapid changes and the roots of the noble morals of leaders are beginning to be uprooted. A situation where there is movement in leadership and leadership arrangements both in bureaucracies and schools. In the world of education there are several aspects that experiencing fundamental changes, to quickly changing the old traditional leadership structure by creating and creating a leadership structure with modern traditions. Besides that, the era of disruption can be considered both a threat and an opportunity, depending on how the managerial leader views the situation and adapts to the modern environment. Managerial leaders or heads Schools that play a role in this must be able to read threat situations well as well as see opportunities that are likely to survive in this era. In the development of Catholic education, especially in the school environment, school principals are indirectly required to resolve various problems or act as defenders in problems. era of disruption which will have an impact on human resources (teachers and staff) and students.